Fatigue behavior of RC slabs flexurally strengthened with prestressed NSM CFRP laminates - Hosseini, Mhoammadreza Mostakhdemin (2022)
Some reinforced concrete (RC) structures requiring strengthening intervention are subjected to cyclic loads during their lifetime. To evaluate the effect of this kind of loading on the behavior of flexurally strengthened RC slabs with prestressed near-surface mounted (NSM) carbon fiber reinforced polymer (CFRP) laminates, an experimental program formed by 10 RC slabs was carried out. Four specimens were submitted to monotonic loading and the remaining were submitted to 1 million cycles at a frequency of 1 Hz. Two levels of fatigue loading were applied and, for each one, three prestress levels for the CFRP were tested (0%, 20%, and 40%). Failure during the fatigue loading was occurred only in one specimen (at 752,000 cycles) with a maximum fatigue stress level of 92% (percentage of the maximum load carrying capacity of the equivalent slab tested up the failure under monotonic static loading). The other specimens, submitted to a maximum fatigue stress level between 46% and 82%, did not fail during the fatigue loading process. After 1 million cycles, the NSM strengthened slabs with 0%, 20%, and 40% of prestress presented an increase of 20%, 18%, and 25%, respectively in mid-span deflection. In general, the strains in the CFRP laminates marginally increased during the fatigue loading. The results of the postfatigue monotonic tests until failure showed that the damage accumulation due the fatigue cycles neither affected the ultimate load capacity of the strengthened NSM CFRP slabs nor the failure mode in which the CFRP rupture.